Model dan Strategi Permodalan Bagi Petani Berbasis E-commerce Dalam Menghindari Ketergantungan Pada Tengkulak dan Meningkatkan Kesejahteraan Petani - Dwi arseto, Dedy; Suci Etri Jayanti; Fonaha Hulu (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This research developed a community-based e-commerce model using a modified Research and Development (R&D) approach through Participatory Action Research (PAR). This model combines two main functions: (i) providing more inclusive and transparent access to digital-based micro-capital, and (ii) marketing agricultural products directly to consumers or modern markets without going through middlemen. Key features include simple cash flow recording, capital requirement simulations, and real-time market price information. Field trials through focus group discussions (FGDs) and training demonstrated significant improvements in farmers' managerial skills: financial record-keeping practices increased from 28% to 74%, while 61% of farmers felt more flexible in determining the selling price of their crops. The results of this study confirm that farmer welfare cannot be measured solely by increased productivity but is also determined by equitable access to capital, efficient distribution of produce, and financial and digital literacy. Practically, this model can be an alternative strategy to break dependence on middlemen, increase farmer independence, and encourage more inclusive and sustainable rural agricultural development.